1994
DOI: 10.1161/01.cir.90.1.556
|View full text |Cite
|
Sign up to set email alerts
|

Normal and abnormal consequences of apoptosis in the human heart. From postnatal morphogenesis to paroxysmal arrhythmias.

Abstract: Apoptosis and necrosis are two distinctly different forms of cell death, and both occur in the human heart. In contrast to necrosis, apoptosis is not associated with inflammation for two reasons. First, the apoptotic cell does not swell or rupture before it is engulfed by either a macrophage or even a neighboring like cell. Second, the phagocytosis occurs with unusual rapidity. Apoptosis, also thought of as cell suicide, is a tidy way of removing cells no longer useful, in essence a form of selective deletion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
8

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(142 citation statements)
references
References 100 publications
2
132
0
8
Order By: Relevance
“…This study brings to James' original observations concerning postnatal morphological changes that has been described as present in infants dying in crib death age range who had no morphological abnormalities. This is what James first referred as ''molding and shaping'' of the atrio-ventricular (AV) node and His bundle, a process never claimed as unique to crib death but that, on the contrary, must be considered a normal postnatal morphological change [10,17,18]. This postnatal morphogenesis is mediated by apoptotic death of myocytes in both the sinus node and the AV junctional tissue [39,40].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This study brings to James' original observations concerning postnatal morphological changes that has been described as present in infants dying in crib death age range who had no morphological abnormalities. This is what James first referred as ''molding and shaping'' of the atrio-ventricular (AV) node and His bundle, a process never claimed as unique to crib death but that, on the contrary, must be considered a normal postnatal morphological change [10,17,18]. This postnatal morphogenesis is mediated by apoptotic death of myocytes in both the sinus node and the AV junctional tissue [39,40].…”
Section: Discussionmentioning
confidence: 94%
“…This term indicates a tidying-up process in which loose strands of surplus conducting tissue are gradually reabsorbed to change AV node and His bundle into their more smooth adult configuration [10,17,41,66]. The resorptive degeneration areas have been described as clusters of young fibroblasts depositing collagen caught in the central fibrous body, sometimes isolated from the ''overdeveloped'' specialized structures, sometimes adjacent to them, without association of inflammation nor massive necrosis or hemorrhage [1,17].…”
Section: Resorptive Degenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Programmed cell death is required to control cell number during morphogenesis and to shape developing organs like the heart and limb as well as craniofacial patterning (James, 1994;Guha et al, 2002;Pajni-Underwood et al, 2007). Recently, Tseng et al (2007) found that apoptosis also plays a crucial role in the early phase of tail regeneration.…”
Section: Programmed Cell Death/ Apoptosismentioning
confidence: 99%